The impact of Anticipation Guides on students’ reading activities to improve conceptual understanding - Yuvita Oktarisa (Gravity : Jurnal Ilmiah Penelitian dan Pembelajaran Fisika, 2022)
Conceptual understanding is significant aspect in Physics Education. Student’s understanding on particular content stands as the significant foundation to build holistic comprehension. The Program for International Student Assessment (PISA) coined students’ ability to understand scientific reading as part of scientific literacy. The role of reading activity in science is fundamental as the position of the experiment. It means reading not only facilitates students to master scientific information but also assists them in having problem-solving skills. This work promotes reading activities to structure students’ comprehension. Anticipation guides facilitates students for having empirical competencies, such as applying, analyzing, and evaluating. These competencies improve students’ conceptual understanding.